2014
DOI: 10.1590/0104-07072014001190013
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making of the nursing team after the revitalization of a decentralized management model

Abstract: This study's objective was to identify changes in decision-making arising from the revitalization of the participatory management model and how these changes impacted the daily work of the nursing staff, as well as to identify potential difficulties. This qualitative case study was conducted in a public hospital in the State of São Paulo, Brazil. Participant observation and semistructured interviews were conducted with 23 nursing workers and the Health Technical Assistant. We used thematic content analysis for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
18

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 14 publications
0
8
0
18
Order By: Relevance
“…As recomendações mencionadas na investigação supracitada possivelmente vão ao encontro de alguns aspectos do modelo de gestão compartilhada, que consiste na descentralização das decisões e aproximação dos integrantes da equipe que compõem o trabalho em saúde, 16 o que incorre na necessidade de aprimorar as linhas de comunicação e a abertura para tal. Dessa forma, possivelmente os problemas do cotidiano serão problematizados pelo grupo de trabalho, favorecendo a sua resolução.…”
Section: Resultsunclassified
“…As recomendações mencionadas na investigação supracitada possivelmente vão ao encontro de alguns aspectos do modelo de gestão compartilhada, que consiste na descentralização das decisões e aproximação dos integrantes da equipe que compõem o trabalho em saúde, 16 o que incorre na necessidade de aprimorar as linhas de comunicação e a abertura para tal. Dessa forma, possivelmente os problemas do cotidiano serão problematizados pelo grupo de trabalho, favorecendo a sua resolução.…”
Section: Resultsunclassified
“…This can interfere in the quality of the services 24 . Thus, in the light of the results, it is suggested that complying with participatory management principles can be yet another tool that, in combination with the Accreditation process, can add quality to the services.…”
Section: Discussionmentioning
confidence: 99%
“…This is relevant as, since the hospital had previously been certified as Accredited with Excellence, which according to ONA reached parameters of excellence in management, 3 the decisions were expected to be based on the principles of collegiate management, which consists in the decentralization of the decisions and approximation of the team members in the health work. 17 In short, it was verified that the professionals perceived the disqualification process of the Accreditation certificate as a punctual decision of the top hospital management and this made these subjects express resentment in this regard. The feelings expressed in the testimonies may be legitimate and justifiable because the successful achievement and maintenance of the certification by the hospital accreditation demands hard teamwork; strengthening of multidisciplinarity; overcoming of paradigms and incorporation of the comprehensive care logic to achieve the desired quality.…”
Section: Disqualification Of the Certification By The Accreditation: mentioning
confidence: 93%